Kadar C-Reaktif Protein Anak Kandung Penderita Dengan dan Tanpa Penyakit Jantung Koroner - Juwairiyah Juwairiyah; Lisyani BS; Indranila KS; Imam BW (MEDIA MEDIKA INDONESIANA, 2009)
C-reactive protein levels in children of patients with and without coronary heart diseaseBackground: Coronary heart disease (CHD) has become the main cause of death worldwide, with atherosclerosis which is a chronic inflammation as the hiden background. CRP (C-reactive protein), a serum inflammation marker, appear in coronary heart disease. So for, the studies about the relation of CRP and CHD had been conducted, but the condition of the CRP serum level in children of CHD patients still rarely be evaluated. The aims to analyse the means CRP levels in children of patients with or without CHD, and to find the influence of CHD patients to the children’s CRP level after controlled by body mass index and lipid profile.Methods: A cross sectional approach to 20 blood specimens from each group, children of patients with and without CHD. The serum CRP levels means were measured twice in range of 2 weeks, using hs-CRP PETIA technique and analysed with Mann-Whitney test and logistic regression.Results: Median CRP levels in children of CHD parents was 2.15 mg/L, which was different from children without CHD parent (1.48 mg/L which was p=0.001). The proportion of parents with CHD to high CRP level in their own children 87%. Logistic regression analysis shows that parents with CHD was not a determinant to high CRP level (p=0.172; 95% CI=0.487-55.821).Conclusions: The CRP of level of children whose parents have CHD is higher than those with parents without CHD.Keywords: Inflammation, CRP levels, parents with coronary heart disease, inheritedABSTRAKLatar belakang: Penyakit jantung koroner (PJK), penyebab kematian utama di dunia dengan aterosklerosis sebagai penyebab tersembunyi merupakan inflamasi kronik. CRP (C-reactive protein), suatu petanda inflamasi akut didapatkan pada PJK. Penelitian yang menghubungkan CRP dan PJK sudah banyak, tetapi penelitian CRP anak dengan riwayat orang tua PJK masih terbatas. Tujuan penelitian ini untuk menganalisis perbedaan rerata kadar CRP anak kandung penderita dengan dan tanpa PJK serta pengaruh orang tua PJK terhadap kadar CRP anak kandung setelah dikontrol dengan IMT (indeks masa tubuh) dan profil lipid.Metode: Pendekatan belah lintang, masing-masing 20 spesimen darah anak kandung penderita PJK dan tanpa PJK. Diukur rerata kadar CRP pada dua kali pemeriksaan dengan interval dua minggu, menggunakan metoda hs-CRP teknik PETIA dan analisis statistik uji beda Mann-Whitney serta regresi logistik.Hasil: Median kadar CRP anak kandung penderita PJK berbeda dengan anak tanpa orang tua PJK (p=0,001). Proporsi orang tua PJK dengan kadar CRP yang tinggi pada anak kandung 87%. Hasil analisis regresi logistik menunjukkan bahwa orang tua PJK tidak merupakan determinan terhadap kadar CRP yang tinggi pada anak (p=0,172; 95% CI=0,487-55,821) .Simpulan: Kadar CRP anak dengan orang tua PJK lebih tinggi daripada mereka yang orang tua bukan penderita PJK.